Reimagining apocalypticism : apocalyptic literature in the dead sea scrolls and related writings - DiTommaso, Lorenzo; Goff, Matthew J. (Atlanta : SBL Press, 2023)
The Dead Sea Scrolls have expanded the corpus of early Jewish apocalyptic literature and tested scholars' ideas of what apocalyptic means. With all the scrolls now available for study, contributors to this volume engage those texts and many more to reexplore not only definitions of the genre but also the influence of the Dead Sea Scrolls on the study of apocalyptic literature in the Second Temple period and beyond. Part 1 focuses on debates about categories and genre. Part 2 explores ancient Jewish texts from the Second Temple period to the early rabbinic era. Part 3 brings the results of scroll research into dialogue with the New Testament and early Christian writings. --
Introduction: Reimagining "apocalypticism" and rethinking "apocalyptic" / Lorenzo DiTommaso and Matthew Goff -- Part 1. Apocalypse and its discontents : texts, contexts, and retrospectives. -- Apocalypses in the Dead Sea Scrolls / John J. Collins -- "The heavens were opened and I saw visions of God": The open heaven four decades on / Christopher Rowland -- Revealed things in apocalyptic literature / Lorenzo DiTommaso -- Revelatory literature in which a revelation is mediated by an otherworldly being: Revelation in the Dead Sea Scrolls / Stefan Beyerle -- Qumran and the apocalyptic / Devorah Dimant -- Apocalypse and authoritative literatures in second temple Judaism / Armin Lange -- The use of genre for many text meanings: Apocalypse and 1 Enoch / Alex Samely -- Part 2. Apocalyptic texts and traditions in ancient Judaism.-- Aramaic as a language of antediluvian wisdom: The early Enoch apocalypses, astronomy, and the deep past in the Hellenistic Near East / Matthew Goff -- It's the end of the world (as the Persians know it)? Iranian influence on Jewish apocalypticism in light of the complete publication of the Dead Sea Scrolls / Jason M. Silverman -- A new proposal: Rereading dreams and visions in early Jewish literature (4Q530, 4Q544, 4Q204, and 1 Enoch 1-36) / Frances Flannery -- Immersing oneself in the narrative world of second temple apocalyptic visions / Angela Kim Harkins -- Poor subjects of the Hodayot: Apocalyptic class subjectivities in practice / G. Anthony Keddie -- The changing apocalypse: Apocalyptic literature as a provisional genre in early rabbinic Judaism / Rebecca Scharbach Wollenberg -- Part 3. The Jewish apocalyptic tradition and early Christianity. -- The Jewish apocalyptic tradition and early Christianity: Divine kingdom: Between the songs of the sabbath sacrifice and the synoptic gospels / Giovanni B. Bazzana -- Aramaica Qumranica apocalyptica and the book of Revelation / Garrick V. Allen -- Heavenly ascent revisited / Martha Himmelfarb -- Apocalypses and apocalyptic literature in the early church: Apocalypse and apocalyptic as rhizome / Harry O. Maier -- The importance of the Gnostic apocalypses from Nag Hammadi for the study of early Jewish mysticism / Dylan M. Burns.
Includes bibliographical references and index.
Online resource; title from PDF title page (ProQuest Ebook Central, viewed April 9, 2024).
eBooks on EBSCOhost
Keywords: Dead Sea scrolls; Dead Sea scrolls -- Criticism and interpretation; Bible. -- Criticism, interpretation, etc., Jewish; Bible. -- Critique, interprétation, etc. juives; Bible; Dead Sea scrolls; Apocalyptic literature -- History and criticism; Judaism -- History -- Post-exilic period, 586 B.C.-210 A.D.; Eschatology, Jewish -- History; Eschatology -- History of doctrines -- Early church, ca. 30-600.; Littérature apocalyptique -- Histoire et critique; Judaïsme -- Histoire -- 586 av. J.-C.-210 (Période postexilique); Eschatologie juive -- Histoire; RELIGION / Biblical Studies / Exegesis & Hermeneutics; Apocalyptic literature; Criticism, interpretation, etc